(untitled) (Journal of Health, Population and Nutrition, 2010)
The study was undertaken to determine transmission of Mycobacterium tuberculosis within the prison environment. In total, 168 Aba Federal prison inmates in Nigeria were evaluated for tuberculosis (TB) by sputum- smear microscopy and sputum culture, simultaneously, and for HIV status by serology. They were subsequently followed up for one year for fresh Mycobacterium-associated infection by tuberculin skin testing or for development of TB and for HIV infection or AIDS. Ninety-one (54.2%) of the 168 prison inmates had infection due to Mycobacterium, and three (3.3%) of them were sputum-smear- and culture-positive while 41 (24.4%), including one (2.4%) with concomitant TB, were HIV-infected. In a one-year follow-up study, 11 (19.3%) of 57 tuberculin skin test (TST)- and HIV-negative inmates became TST-positive and one (1.8%) HIV-positive, eight (13.8%) of the 58 TST-positive but HIV-negative inmates developed TB, and one (1.7%) became HIV-infected: six (24.0%) of 25 TST- and HIV-positive inmates developed TB while five (33.3%) of 15 TST-negative but HIV-positive inmates became TST-positive, and one (6.7%) progressed to AIDS. The duration of imprisonment did not influence the rates of infection, and the transmission of Mycobacterium tuberculosis did not necessarily require sharing a cell with a TB case. Key words: HIV; Mycobacterium tuberculosis; Prisoners; Tuberculosis; Tuberculin skin test; Nigeria DOI: 10.3329/jhpn.v28i4.6038 J HEALTH POPUL NUTR 2010 Aug;28(4):327-332